PERSEPSI MAHASISWA TERHADAP MEDIA PEMBELAJARAN MATAKULIAH USAHATANI ”SI-CANTIK” PADA PROGRAM STUDI AGRIBISNIS - Elys Fauziyah; Mokhammad Rum; Fuad Hasan; Sri Ratna Triyasari (STKIP Pesisir Selatan, 2020)
Learning media is a tool that can be used to optimize learning activities. The development of information technology can be utilized to design contemporary learning media, as has been done by lecturers of farming course in the Agribusiness Study Program at the University of Trunojoyo Madura (UTM). The lectures designed an information technology-based learning media, named Si-Cantik. This media has been applied to farming courses on odd semester 2019/2020. In order to find out students' perceptions of this media, a survey was conducted using seven indicators. The number of samples is 33 respondents. The results of the analysis showed that most respondents agreed that Si-Cantik learning media could provide a more detailed understanding of farming plan material, and could improve skills in farming plan made.